Potret Sosial-Edukasi Pesantren di Desa Sirnasari: Identifikasi Peran dalam Membangun Ketahanan Masyarakat - Putri Dian Wulansari; Sonia Ari Murti; Yayu Febriani; Abdul Basit; Siti Mulyati; Diva Rizka Affifah; Rizki Maulana; Mita Nurussyfa (Journal of Empowerment Community, 2026)
The Community Service Program (KKN) conducted by Universitas Perjuangan Tasikmalaya in Sirnasari Village, Sariwangi District, Tasikmalaya Regency aimed to identify the role of pesantren (Islamic boarding schools) as centers of education and social resilience within rural communities. Pesantren in this area play a strategic role not only in delivering religious education but also in preserving social, moral, and economic values among local residents. The program, held from July 22 to August 26, 2026, involved 15 students from five faculties who collected data through observation and interviews with pesantren leaders, teachers, students, and nearby residents. The findings indicate that pesantren in Sirnasari Village contribute significantly to moral education and community-based religious activities while also engaging in small-scale economic initiatives such as herbal product sales and garden produce management. However, limitations remain in infrastructure, management capacity, and institutional collaboration. This activity provides an initial overview of pesantren’s potential as community-based centers of education and social resilience and serves as a foundation for future community service programs focused on digital literacy, student entrepreneurship, and institutional capacity strengthening within rural pesantren.